2009
DOI: 10.1177/0021998309341850
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Abrasive Wear Behavior of Coleus Spent Filled Unsaturated Polyester/Polymethyl Methacrylate Semi Interpenetrating Polymer Network Composites

Abstract: Mechanical properties and three-body abrasive wear behavior of 5 and 10% w/w bio-based coleus spent (CS) filled and unfilled semi interpenetrating polymer network composites of unsaturated polyester/polymethyl methacrylate (80/20) have been studied. The tensile strength and elongation at break has been evaluated using 4302 Hounsfield Universal testing machine. The effect of abrading distances viz., 150, 300, 450, and 600 m and different loads of 22 and 32 N at 200 rpm on the abrasive wear behavior have been st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Our research school is the first to report the use of NIS as filler material in the fabrication of thermoplastic and thermoset composites [33,[54][55][56][57][58][59][60]65] and for the use as effective adsorbents for remediation of Congo red, methylene blue and ethidium bromide dyes [32,53,64]. Despite myriad research papers reported the use of low-cost agriculture waste as biosorbent for the remediation of toxic dyes; very limited information is available about the use of dye adsorbed biosorbent commonly known as "sludge".…”
Section: Introductionmentioning
confidence: 99%
“…Our research school is the first to report the use of NIS as filler material in the fabrication of thermoplastic and thermoset composites [33,[54][55][56][57][58][59][60]65] and for the use as effective adsorbents for remediation of Congo red, methylene blue and ethidium bromide dyes [32,53,64]. Despite myriad research papers reported the use of low-cost agriculture waste as biosorbent for the remediation of toxic dyes; very limited information is available about the use of dye adsorbed biosorbent commonly known as "sludge".…”
Section: Introductionmentioning
confidence: 99%
“…The coleus spent (CS) filled unsaturated polyester/polymethyl methacrylate (USP/PMMA) semi‐interpenetrating polymer network (SIPN) composites showed better abrasion wear resistance as compared to unfilled SIPN system 14. The sugarcane fiber reinforcement in the thermoset polymers had shown enhancing wear resistance 15…”
Section: Introductionmentioning
confidence: 99%
“…By combining lignocellulosic materials with plastics, it is possible to get many environmental friendly benefits including making of light weight final product, lowering the manufacturing machinery erosion, cost reduction, biodegradability and prevention/minimization of burnt residue production or toxic by-products. Our research school has reported about this aspect [36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 95%